Clonal dissemination of KPC-2 producing Klebsiella pneumoniae ST11 clone with high prevalence of oqxAB and rmtB in a tertiary hospital in China: results from a 3-year period. Issue 1 (December 2016) - Cheng, Li; Cao, Xiao-Li; Zhang, Zhi-Feng; Ning, Ming-zhe; Xu, Xue-Jing; Zhou, Wanqing; Chen, Jun-Hao; Zhang, Jin-hua; Shen, Han; Zhang, Kui
Abstract Background Carbapenemase-producingKlebsiella pneumoniae (CPKP)strains have emerged as a major problem for healthcare systems. The aim of this study was to determine the circulating clones and analyze the clinical and molecular characteristics of CPKP in our hospital. Methods A total of 74 carbapenemase producers collected from our hospital from 2012 to 2014 were analyzed for the prevalence of extended-spectrum β-lactamase (ESBLs), plasmid-mediated quinolone resistance genes (PMQRs), exogenously acquired 16S rRNA methyltransferase (16S-RMTase), and plasmid-mediated AmpC enzyme (pAmpCs) by PCR and DNA sequencing. The sequence types (STs) of the carbapenemase producers were analyzed by multi-locus sequence typing (MLST). And Pulsed-field gel electrophoresis (PFGE) was performed to investigate the genetic relationship of KPC-2 producing strains. Clinical data were retrieved from the medical records. Results KPC-2 (n = 72) was the predominant enzyme followed by NDM-1 (n = 2); The genesbla CTX-M, bla SHV, bla TEM-1, bla DHA-1, rmtB, armA, oqxA, oqxB, andqnrB were present in 29 (39.2 %), 27 (36.5 %), 46 (62.2 %), 2 (2.7 %), 25 (33.8 %), 1 (1.4 %), 60 (81.1 %) and 56 (75.7 %), 6 (8.1 %) isolates, respectively. MLST analysis revealed 10 different STs. The most dominant ST was ST11 (78.4 %, 58/74), followed by ST15 (8.1 %, 6/74). PFGE patterns of the KPC-2 producingK. pneumoniae isolates exhibited clonal dissemination of ST11 and ST15 clones as well as a genetic diversity of the remaining strains. Conclusion The intra- and inter-hospital cross-transmission of KPC-2-producingK .pneumoniae ST11 co-carryingoqxAB andrmtB in our hospital strongly suggested that rapid identification of colonized or infected patients and screening of carriers is quite necessary to prevent a scenario of endemicity.